2020
DOI: 10.1523/jneurosci.1796-19.2020
|View full text |Cite
|
Sign up to set email alerts
|

A VTA to Basal Amygdala Dopamine Projection Contributes to Signal Salient Somatosensory Events during Fear Learning

Abstract: The amygdala is a brain area critical for the formation of fear memories. However, the nature of the teaching signal(s) that drive plasticity in the amygdala are still under debate. Here, we use optogenetic methods to investigate the contribution of ventral tegmental area (VTA) dopamine neurons to auditory-cued fear learning in male mice. Using anterograde and retrograde labeling, we found that a sparse and relatively evenly distributed population of VTA neurons projects to the basal amygdala (BA). In vivo opt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(94 citation statements)
references
References 76 publications
4
90
0
Order By: Relevance
“…Though we studied mainly PFC in this article, there are other important areas involved in fear conditioning such as the amygdala; despite the evidence for a dopamine signaling role in amygdala during aversive learning, the role of dopamine neurons in aversively motivated behavior is still controversial 86 . We cannot state that slight differences in PFC of our MAT versus MIX rats are causal, but it is well known that connections between the amygdala and medial prefrontal cortex (mPFC) are crucial for both fear conditioning and extinction 87 …”
Section: Discussionmentioning
confidence: 99%
“…Though we studied mainly PFC in this article, there are other important areas involved in fear conditioning such as the amygdala; despite the evidence for a dopamine signaling role in amygdala during aversive learning, the role of dopamine neurons in aversively motivated behavior is still controversial 86 . We cannot state that slight differences in PFC of our MAT versus MIX rats are causal, but it is well known that connections between the amygdala and medial prefrontal cortex (mPFC) are crucial for both fear conditioning and extinction 87 …”
Section: Discussionmentioning
confidence: 99%
“…There are other important players in fear memory learning as well, including BLA GABAergic interneurons (Bocchio et al, 2017). Neurotransmitters such as dopamine, noradrenaline, and acetylcholine are also important (de la Mora et al, 2010;Heath et al, 2015;Kwon et al, 2015;de Oliveira et al, 2017;Wilson and Fadel, 2017;Giustino and Maren, 2018;Brandão and Coimbra, 2019;Stubbendorff et al, 2019;Tang et al, 2020). Serotonin and glutamate influence fear memory (Walker and Davis, n.d.;Maren, 1996;Bauer, 2015;Johnson et al, 2015;Bocchio et al, 2016), as does the transcription factor CREB (cyclic AMP response element-binding protein) (Vazdarjanova and McGaugh, 1998;Bocchio et al, 2017;Ressler and Maren, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence implicating both VTA dopamine neurons and the amygdala in aversive learning though, the precise role of dopaminergic projections from the VTA to the BLA in this process remained unclear. In a recent issue of The Journal of Neuroscience, Tang et al (2020) used molecular, electrophysiological, and optogenetic techniques to elucidate the contribution of this circuit to classical fear conditioning.…”
mentioning
confidence: 99%
“…First, Tang et al (2020) sought to map the VTA-to-BLA pathway, using anterograde and retrograde circuit-tracing methods. Anterograde labeling of VTA dopamine neurons revealed that, within the amygdala, these neurons primarily innervate the basal nucleus (BA) and the medial portion of the CeA.…”
mentioning
confidence: 99%